Strategi Guru dalam Mengembangkan Bakat Siswa - Uci Purnama Sari; Risma Dayani; Heni Rahma Dita; Helen Mantika; Pegi Vendrik (CV. ITTC INDONESIA, 2026)
The problem in this study is the low attention to the development of students’ talents in elementary schools, which tend to focus only on academic achievement, resulting in underdeveloped non-academic potential among students. This study aims to analyze teachers’ strategies in developing students’ talents in the classroom and to provide an overview of applicable steps in the learning process. The method used in this study is a literature review by examining 20 relevant sources, including accredited national journals, educational books, and scientific articles published within the last ten years. The data analysis technique used is content analysis, which involves reading, classifying, comparing, and synthesizing information from various sources. The results show that effective strategies in developing students’ talents include systematic identification of potential, implementation of differentiated instruction, provision of motivation and positive reinforcement, creation of a conducive learning environment, implementation of extracurricular activities, and collaboration between teachers, parents, and the community. These strategies have been proven to improve students’ self-confidence, creativity, and independence in developing their potential.